A Sensitive, Highly Specific Novel Isothermal Amplification Method Based on Single-Nucleotide Polymorphism for the Rapid Detection of Salmonella Pullorum - Shen, Haiyan (Front Microbiol, 2020)
S. Pullorum (Salmonella enterica serovar Gallinarum biovars Pullorum) is an infectious pathogen that causes the acute systemic disease called Pullorum disease in poultry. This disease causes huge losses to the poultry industry and seriously affects the yield and quality of the chicken product. It is not easily distinguishable with fowl typhoid caused by S. Gallinarum (Salmonella enterica serovar Gallinarum biovars Gallinarum), hence the development of a specific and rapid detection method for this pathogen is highly desired. In this study, we propose a novel single-nucleotide polymorphism (SNP) detection strategy termed loop primer probe-introduced loop-mediated isothermal amplification (LP-LAMP) for S. Pullorum detection. Based on the original primer sets, we targeted the nucleotide position 237 of the rfbS gene sequence to design a new modified loop-primer probe with a ribonucleotide insertion, where activity of the enzyme ribonuclease H2 (RNase H2) is only activated when the probe is perfectly complementary, leading to the hydrolytic release of a quencher moiety and thus an amplified signal. The method exhibits robust specificity and a low detection limit as the copy number and genomic DNA is 21 copies/μL and 4.92 pg/μL, respectively. This method showed great performance in real sample testing of 130 samples of embryos, livers, and anal swabs from chickens in poultry farms. The experimental results are mainly consistent with traditional identification methods and a PCR method reported in the past. However, the other two methods still contain some false negative results, while our method is without miss detection. The entire closed-tube reaction process can be accomplished within 40 min at a constant temperature (61°C) without the need for expensive instruments or a complicated operation. The LP-LAMP strategy established in this study not only overcomes the existing difficulties of S. Pullorum rapid detection, it also provides a novel, sensitive, and highly specific detection platform for SNPs that is suitable for clinical use.